Characterization, demulsification and transportation of heavy crude oil via oil-in-water (o/w) emulsion - Chew Fern, Tan (2012)
The production of heavy crude oil is limited due to its high viscosity. It is expected to increase in the future as low viscosity crudes are depleted. The high viscosity lead to increase of pump energy as it creates high pressure drop. In order to reduce the viscosity of the heavy crude, it is suggested to mix it with water and optimum emulsifiers to create a lower viscous fluid, oil-in-water (O/W) emulsions. In this study, both chemical and physical properties of O/W emulsion that prepared by using cocoamide DEA (nonionic and biodegradable surfactant that synthesis from coconut oil) and two types of conventional chemical emulsifiers (Span 83 and Triton X-100) were investigated. O/W emulsions with two different ratios (50-50% and 65-35%) were prepared at three different mixing speed (500rpm, 1000rpm and 1500rpm) with the concentrations (0.2 wt%, 0.5 wt% and 1.0 wt%) of each emulsifier. These emulsions were tested for relative rates of water separation (stability test), viscosity, shear stress and shear rate at varied temperature and stirring speed of Brookfield viscometer. While the droplet size was carried out by using Carl Zeiss Research Microscope and its software. Results sho that Span 83 at 1.0 wt% mixed with 65-35% O/W with 1500rpm mixing speed obtained the most stable emulsion for transportation compared to the other two. Then, its chemical properties were tested via Fourier Transform Infrared (FTIR). These chemical properties are important in order to predict the occurrence of wax deposition during the transportation. The transportation of the emulsion then carried out by using the laboratory scale pipeline. Demulsification is the process of separation of water from crude oil. Crude oil need to be separate efficiently and quickly from the water to allow further treatment. This is to ensure the crude oil value can be maximized and the operating cost can be minimized. Demulsifiers (Hexylamine and Coco Amine) with different concentrations (0.2 wt% and 0.5 wt%) were used for transportation. The relative rates of water separation were characterized via beaker test. Coco amine that synthesized from coconut oil promotes the best coalescene of droplets compared with the conventional demulsifier that used in this study which is hexylamine.